2002
DOI: 10.1046/j.1365-2885.2002.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of trimethoprim‐sulfadoxine against Escherichia coli in a tissue cage model in calves

Abstract: Tissue cages implanted subcutaneously in calves were infected with Escherichia coli. Twenty-four hours later, the calves were treated either with single doses of 2.5 + 12.5 or 5 + 25 mg/kg trimethoprim (TMP) + sulfadoxine (SDX) or with five doses of 7.5 + 37.5 mg/kg TMP + SDX at 12-h intervals. In addition, one cage in each of three calves in the highest dose group was infected 3 h after initiation of treatment. Untreated calves were kept as controls. Concentrations of TMP and SDX in plasma and tissue cage flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…Besides the antimalarial activity, the sulfadoxine-pyrimethamine hybrid is also active against the parasite Toxoplasma gondii [15] and is considered as primary prophylaxis of pneumonia caused by Pneumocyctis carinii [16][17][18] and toxoplasmatic encephalitis in patients infected with HIV [17,18]. Sulfadoxine is also used in combination with trimethoprim to treat different bacterial infections in animals as horses and calves, being active against Gram-negative and Gram-positive bacteria [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the antimalarial activity, the sulfadoxine-pyrimethamine hybrid is also active against the parasite Toxoplasma gondii [15] and is considered as primary prophylaxis of pneumonia caused by Pneumocyctis carinii [16][17][18] and toxoplasmatic encephalitis in patients infected with HIV [17,18]. Sulfadoxine is also used in combination with trimethoprim to treat different bacterial infections in animals as horses and calves, being active against Gram-negative and Gram-positive bacteria [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Greko and colleagues previously showed that tissue infections in secluded infection sites of calves were refractory to treatment with trimethoprim-sulfadoxine due to elevated thymidine concentrations (13). Thymidine concentrations were previously reported to be high in the blood of several animals (24).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of these antibiotics can be antagonized by the bacterial utilization of extracellular thymidine (2,13,18,33,36,39). Various bacteria have the ability to use an alternative pathway by the uptake of extracellular thymidine and the subsequent intracellular phosphorylation to dTMP by thymidine kinase (19,39).…”
mentioning
confidence: 99%
“…In general, a microorganism is considered susceptible when displaying a TMP/SDZ MIC lower than 0.5/9.5 mg/ml (Prescott, 2000). However, synergy is observed over a wide range of ratios, provided that both drugs are present at levels above their MICs (Bushby, 1980;Greko et al, 2002). Following i.v.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetics of SDZ and/or TMP have been most extensively studied in cattle and calves (Clarke et al, 1989;Kaartinen et al, 1999Kaartinen et al, , 2000Greko et al, 2002). Studies in other species, such as swine (Nielsen and Rasmussen, 1975a,b;Garwacki et al, 1996), dogs and cats (Craig and White, 1976;Sigel et al, 1981), horses (Brown et al, 1983;Bogan et al, 1984;Van Duijkeren et al, 1994a, Gustafsson et al, 1999, poultry (Lo« scher et al, 1990;Batzias et al, 2000;Baert et al, 2003), rabbits (Ladefoged, 1977) and ¢sh (Nouws et al, 1993), have also been performed.…”
Section: Introductionmentioning
confidence: 99%